Communication Skills Improvement Through the Teaching Factory Model - Sri Subekti,; Ana A,; Mokhamad Syaom Barliana, (Online Journal for TVET Practitioners, 2019)
Abstract: The fourth industrial revolution compels prospective workers to obtain industry demanded skills. Vocational education and training play an important role in preparing workers. Most training institutions are lagging behind in terms of predicting and training future skills that will be demanded by employers. Employability skills enable employees to properly execute their assigned tasks and duties at work place. Communication skills are a sub-type of employability skills. This article focused on improving vocational students’ communication skills through the teaching factory model. The concurrent triangulation study design was used. The sample was made up of 60 Agricultural Processing students enrolled in vocational schools in West Java. Six indicators were used to measure communication skills. There were at least twenty units of competence as a reference for measurement. Communication skills improvement was observed following the implementation of the teaching factory model. Between 83% and 94% of the students showed immense communication skills improvement. Optimization in student involvement, learning environment conditioning, and tutoring contributed to the improvement of students’ communication skills (employability skills).